IWD2021 – Tatu Ibrahimu on leading a AKM Glitters unit brooder in Tanzania - International Livestock Research Institute (International Livestock Research Institute, 2021)
Tatu Ibrahimu, a unit brooder leader under AKM Glitters in Tanzania, says that with the COVID-19 pandemic, she now finds it hard to sell her four-week-old chickens to smallholder farmers because movement restrictions have hindered smallholder farmers from accessing the brooders.